2015
DOI: 10.1159/000369576
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tumor Necrosis Factor-α on Podocyte Expression of Monocyte Chemoattractant Protein-1 and in Diabetic Nephropathy

Abstract: Background/Aims: Tumor necrosis factor (TNF)-α is believed to play a role in diabetic kidney disease. This study explores the specific effects of TNF-α with regard to nephropathy-relevant parameters in the podocyte. Methods: Cultured mouse podocytes were treated with recombinant TNF-α and assayed for production of monocyte chemoattractant protein-1 (MCP-1) by enzyme-linked immunosorbent assay (ELISA). TNF-α signaling of MCP-1 was elucidated by antibodies against TNF receptor (TNFR) 1 or TNFR2 or inhibitors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 48 publications
1
30
0
Order By: Relevance
“…Indeed, the kidney is not a main target organ of insulin, and thus insulin action on p-Akt in the kidney is weak. In addition, it is undeniable that HKC may have the independent antergic effect of TNF-α, an inducer of p-AKT (Chung et al, 2015), moreover, the reduction of TNF-α may also be the potential mechanism of HKC for the protection of the kidney. All in all, regarding these interesting issues, we could not draw a clear conclusion in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the kidney is not a main target organ of insulin, and thus insulin action on p-Akt in the kidney is weak. In addition, it is undeniable that HKC may have the independent antergic effect of TNF-α, an inducer of p-AKT (Chung et al, 2015), moreover, the reduction of TNF-α may also be the potential mechanism of HKC for the protection of the kidney. All in all, regarding these interesting issues, we could not draw a clear conclusion in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the activation of various inflammatory molecules, such as cytokines (IL-6, IL-8, IL-1b, and TNF-a) [24], adhesion molecules (ICAM-1) [25], chemokines (MCP-1) [26], synthetase (iNOS and COX-2), and growth factors (VEGF, TGF-b) [27] contribute to the progression of DN. In our study, LPS up-regulated the production of a spectrum of inflammatory molecules in hRPTECs, including IL-6, IL-8, IL-1b, TNF-a, iNOS, COX-2, MCP-1 and ICAM-1.…”
Section: Discussionmentioning
confidence: 99%
“…This may be, in part, due to TGF-β1/Smad3-induced ECM production occurring by way of Smad3 binding to the COL1A2 promoter, which, while functional in Col1a2-deficient mice, may not increase homotrimeric type I collagen production. Col1a2-deficient/Smad3-deficient 16,53 and Smad-3-independent TGF-β1 signaling (such as Ras/Raf, extracellular signal-regulated kinase-mitogen-activated protein kinase, and nuclear factor κB) remain to be investigated. 46,52 TNF-α has been shown to be released by mesangial cells upon exposure to certain pathogens.…”
Section: Discussionmentioning
confidence: 99%